Teaching English through Online: Challenges or Opportunities? (Siddhajyoti Interdisciplinary Journal, 2023)
This study attempts to explore the demand of online education growing aftermath of COVID-19 all over the world from school level to university level. With this scenario, this study explored the possibilities and effectiveness of teaching English through online and its impact on students’learning achievement and to explore students and teachers’ perception about online education whether it is a challengeable or an opportunity. By applying phenomenological research design under the qualitative method, purposive sampling technique was used for collecting required data. Three participants were selected to collect data for this study. Semi-structured online interview was conducted to collect the data. I used recorded interview after that recorded data were coded and analyzed into different themes. The major findings ofthis study indicated that lack of accessibility, accountability, adaptability and availability of the online education, insufficient infrastructure, electricity and trained teacher, technical problems and knowledge as well as personal training and monitoring about ICT are prominent to conduct online education in Nepal.